ANALISIS YURIDIS PEMIDANAAN ATAS PELAKU PENADAH BARANG HASIL PENCURIAN SEPEDA MOTOR UNTUK MEWUJUDKAN KETERTIBAN HUKUM - Rizky Pratama; Fadlan Fadlan; Christiani Prasetiasari (Ensiklopedia of Journal, 2022)
In writing this thesis entitled Juridical analysis of the punishment of the perpetrators of collecting goods resulting from theft of motorbikes to realize legal order, the research study of the Barelang Police of Batam City, there is a problem formulation that includes the legal arrangement of punishment for the perpetrators of collecting goods resulting from theft of motorcycles to realize legal order and the second concerning the implementation, constraint factors and solutions. data collection was carried out through interviews with parties related to the research topic. In addition, the author also conducts library research through books related to the research topic. Furthermore, the data obtained were analyzed qualitatively which was then presented descriptively. The results of research and discussion in the implementation of punishment for perpetrators of collecting goods from motorbike theft to realize legal order show the results of this study in the form of the application of the criminal act of confiscation contained in Article 480 of the Criminal Code paragraph (1), especially in the Barelang Police Station area, which is very good and based on regulations invite. As for the problems discussed in this thesis, namely the process of criminalizing the perpetrators of collecting goods resulting from theft of motorbikes to create legal order and discussing the factors of obstacles and solutions faced by investigators in carrying out convictions for perpetrators of criminal acts of detention. From this research, it shows that the perpetrator is not the main actor but participates in a criminal act, namely detention in this case the prosecutor always asks that there must be a suspect or main actor of a criminal act of theft first, if not side by side it will be returned.Keywords: Theft, Crime, Detention